Giant Magnetoresistance of Silver Nickel Iron Grandular Magnetic Thin Films Prepared by RF Magnetron Sputtering System - Lim, Kean Pah (1998)
The discovery of giant magnetoresistance (GMR) in multilayer system and subsequently in granular films has stimulated world wide research activities, due to both its fundamental significance and its potential application to magnetic sensors and data storage. Hence, this work is carried out to investigate this phenomenon. The first part of the work is to find out the suitable parameter and condition for producing good quality films. Granular magnetic thin films of Ag- Ni-Fe have been prepared at different deposition rates and compositions using RF Magnetron Sputtering system. Subsequently, the surfaces of the thin films were examined using the scanning electron microscope (SEM) and energy dispersive X-ray (EDX) analysis, also in the SEM, was used to determine the composition of the films. The crystalline state of the films was determined by X-ray diffraction using CuKa radiation in a 29 powder diffractometer and the resistances of the films were measured using a four-point probe method to calculate the GMR effect. Lastly, the data obtained were analysed to investigate and understand the electrical transport mechanism in thin films. The result shows that the GMR effect is thickness, structure and composition dependent. The highest GMR value was obtained for the samples deposited for 60 minutes with 25% of magnetic entities embedded in the non-magnetic matrix. The microstructure analysis shows that the highest GMR value was obtained if the formation of <111> fcc Ag texture is dominant and small grain size was formed in the film. In conclusion, a good granular thin film with high GMR value of 3.73% at room temperature has been developed and this result meets the requirement in the magnetic sensors and data storage industry.